Simulasi Penentuan Optimasi Arah Taksi Kosong Dengan Gps Dan Metode Monte Carlo - Hutapea, Sabungan Halomoan; Sinaga, Rosita (Warta Penelitian Perhubungan, 2010)
The development of metropolitan cihJ as Jakarta for years is high, thus the demand Jo transportationservices. Tcui is one of mode transportation which is mostly used by middle to high class people. Theproblem is, sometimes many people are wasting time for waiting empty taxi, mean while manyempty taxi, are searching for the passenger.The objective of this simulation model is to direct the taxi, movement to get passenger with the help ofi~b "based software. So then, there is information to direct the taxi, mavement to choose the right Wat}to get passenger with high possibilihJ rate of passenger.The taxi, driver is equipped by GPS that will find out the coordinate position data of geographical. Toinput the data such as position of start-finish and arrival time of passenger it can be done by cellμlarphone then data will be transmit to ~bsite.Using simulation approaching, a Monte Carlo simulation model can be build that will optimize taxi,driver to find passenger. This modeling will be able to estimate the possibilihj of passenger arrival anddistribution of taxi, cars in one area. The comparison of simulation without modeling resuled intincreament of some aspects, such as increment of delivetJ services increase to 81.48%, searching timeand waiting time become 4.12% and 6.45% respectively.Keyword: taxi, movement, waiting time, travel time, Monte-Carlo Simulation